DNA sequencing of type material and newly collected specimens reveals two heterotypic synonyms for Harveylithon munitum (Metagoniolithoideae, Corallinales, Rhodophyta) and three new species. Issue 4 (9th May 2021) - Richards, Joseph L.; Schmidt, William E.; Fredericq, Suzanne; Sauvage, Thomas; Peña, Viviana; Le Gall, Line; Mateo‐Cid, Luz Elena; Mendoza‐González, Angela Catalina; Hughey, Jeffery R.; Gabrielson, Paul W.
Abstract : Nongeniculate coralline algae are difficult to identify based solely on morpho‐anatomy. To address the systematics of several taxonomically challenging taxa, we analyzed DNA sequences of a short portion (118–296 base pairs) of the 3′ end of the rbc L gene from three type specimens. The analyses revealed that Harveylithon munitum (basionym: Lithophyllum munitum ), described in 1906 from Cave Cays, Exuma Chain, Bahamas, is conspecific with both Goniolithon accretum and Goniolithon affine, described in 1906 from Sand Key, Florida and in 1907 from Culebra Island, Puerto Rico, respectively. Lithophyllum munitum and G. accretum were described in the same 1906 publication and have equal priority. We have selected the currently accepted and most commonly used name H. munitum to apply to this entity. Comparative analyses of rbc L, psb A, UPA, COI, and LSU sequences from contemporary field‐collected specimens revealed that H. munitum currently inhabits mesophotic rhodolith beds in the northwestern Gulf of Mexico, as well as the intertidal zone in the Florida Keys, Honduras, Atlantic Mexico, Caribbean Panama, and Guadeloupe, French West Indies. Species delimitation analyses reveal that the Western Atlantic and Australian H. munitum populations may be separate species. Two new species of Harveylithon from the northwestern Gulf of Mexico and one new species from the southwestern Gulf of Mexico, the Caribbean, and the Red Sea were also identified in the analyses and are described.